PERANCANGAN WELDING JIG UNTUK 2 JENIS KNALPOT DENGAN METODE VDI 222 DI PT. RC UNGGUL DAIHEN INDONESIA - Agus Widodo; Fransisca Omega Putri (Politeknik Meta Industri, 2022)
This study aims to meet customer demand for the manufacture of welding jigs for 2 exhaust types, namely VL20 types 1 and 2, with reference to the previous welding jig, namely rotary welding jig. Where the welding jig rotary process can only be done for the welding process 1 type of exhaust only. Therefore the customer asked for a welding jig that can be used for welding processes with 2 types of exhaust at once. This aims to reduce the production cost of welding jigs. This study uses the VDI 2222 method in the design process, which is divided into several stages, namely analysis, conceptualization, design and completion. The results obtained in this study are the costs of making welding jigs VL20 types 1 and 2 are more expensive than the costs of making rotary welding jigs with a cost difference of Rp. 19,809.992. However, if viewed from the function of the VL20 welding jig type 1 and 2, it is much cheaper than the rotary welding jig because it is used for 2 types of workpieces or 2 different types of exhausts, so if the previous welding jig system was applied to the manufacture of welding jigs for the VL20 type 1 exhaust. and 2 then the manufacture will cost 2 times the cost of a rotary welding jig, which is Rp. 94,547,568 x 2 = Rp.189,095,136. and other advantages, namely saving production area. Keywords : Welding jig, VDI 222, fixture, Cost